Clays and Clay Minerals, Vol. 57, No. 6, 686–694, 2009. - Dohrmann, R.; Ruping, K.B.; Kleber, M.; Ufer, K.; Jahn, R. (My University, 2009)
In X-ray diffraction (XRD) analysis, preparation of oriented clay specimens enhances their 00l reflections by arranging basal surfaces parallel to the specimen surface. In one-dimensional modeling of XRD intensities, degree of preferred orientation is one of the variable parameters and a user may choose different s* values for different minerals. The usual assumption is, however, that the layers of all clay minerals that are present exhibit a similar degree of preferred orientation to that of the clay mineral flakes parallel to the basal plane. If the orientation of individual clay minerals is significantly different, and if this is not taken into account, the relative proportions of the constituent minerals cannot be modeled accurately. The actual or so-called ‘preferred’ orientation is a potentially large source of error in any attempt at quantitative XRD analysis because it cannot be assumed to be constant among different minerals and may also vary as a result of pretreatment. In the present study the influence of sample composition and sample pretreatment on the degree of preferred orientation was determined using the parameter s*. A statistical parameter was calculated to determine and ensure the reproducibility of s* measurements. The most important result was that, when mixed together, clay minerals influence each other in terms of the degree of preferred orientation. Among individual samples, the degree of preferred orientation can be different for each clay mineral. The power of sonication used in sample pretreatment of a pure kaolinite and a pure illite had no significant influence on the degree of preferred orientation. The changes in intensities upon variation of the tilting angle (w) allowed for calculationof s* of smectites inpure samples, inadmi xtures, and in samples treated in two different ways (air-dried and glycerol-intercalated), which is reported here for the first time. Smectites are very fine grained with flexible morphology which is believed to be the reason for their tendency to exhibit poor orientation (s* = 22º); further research is required to establish whether this is a general feature of smectites. After glycerol treatment a soil smectite showed a slightly better orientation compared to the air-dried pattern. The results of the study illustrate the difficulty of predicting changes in preferred orientation of clay mineral admixtures, even if non-platy minerals such as clay-sized quartz are added. Ingen eral, s* decreased when non-platy minerals were added, which is explained by changes in geometry of the specimen. Not all clay minerals, however, showed simultaneous changes in their orientation behavior.
Variation Of Preferred Orientation In Oriented Clay Mounts As A Result Of Sample Preparation And Composition
gsccm57602-doh.pdf- 884KB
Keywords: Periodicals; Geology; Clay Minerals; Oriented Mounts; Preferred Orientation; Quantitative Phase Analysis; Sigma; XRD